2008
DOI: 10.1016/j.cell.2007.12.015
|View full text |Cite
|
Sign up to set email alerts
|

β Cells Can Be Generated from Endogenous Progenitors in Injured Adult Mouse Pancreas

Abstract: Novel strategies in diabetes therapy would obviously benefit from the use of beta (beta) cell stem/progenitor cells. However, whether or not adult beta cell progenitors exist is one of the most controversial issues in today's diabetes research. Guided by the expression of Neurogenin 3 (Ngn3), the earliest islet cell-specific transcription factor in embryonic development, we show that beta cell progenitors can be activated in injured adult mouse pancreas and are located in the ductal lining. Differentiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
910
5
16

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 919 publications
(983 citation statements)
references
References 34 publications
52
910
5
16
Order By: Relevance
“…Nestin, a non-endocrine lineage PPCM, was increased by IMT504 treatment in endothelial cells, pericytes and stellate cells, marking active regeneration [7] and angiogenesis [8]; this last variable was also indicated by increased CD31 in blood vessels. NGN3, an unambiguous marker for islet progenitors, was absent in normal islets and markedly increased in STZ-IMT504 rats, suggesting that IMT504 may be triggering NGN3 synthesis in pancreas-resident progenitor cells [9], similar to what was observed when administrating bone marrow-derived cells [10]. Our results are consistent with the view that the adult pancreas retains the potential to reactivate its embryonic mode of beta cell formation under the proper stimuli [11], and this capacity is greatly enhanced by IMT504.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nestin, a non-endocrine lineage PPCM, was increased by IMT504 treatment in endothelial cells, pericytes and stellate cells, marking active regeneration [7] and angiogenesis [8]; this last variable was also indicated by increased CD31 in blood vessels. NGN3, an unambiguous marker for islet progenitors, was absent in normal islets and markedly increased in STZ-IMT504 rats, suggesting that IMT504 may be triggering NGN3 synthesis in pancreas-resident progenitor cells [9], similar to what was observed when administrating bone marrow-derived cells [10]. Our results are consistent with the view that the adult pancreas retains the potential to reactivate its embryonic mode of beta cell formation under the proper stimuli [11], and this capacity is greatly enhanced by IMT504.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, progenitor recruitment from other compartments may also occur. Lineage-tracing studies would provide important information in this regard [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…A ligature around the main pancreatic duct results in distal damage, acinar involution, and an associated inflammatory response. Xu et al (2008) demonstrated that Ngn3 þ cells were induced in the duct epithelium after PDL, and thus identified a potential source of new endocrine cells in vivo. These Ngn3 þ duct cells, upon isolation, could produce all endocrine cell types when cultured in Ngn3 null pancreatic bud explants in vitro.…”
Section: Injury-induced Reprogrammingmentioning
confidence: 94%
“…Direct lineage tracing, in which Cre recombinase was driven by a duct cell-specific promoter (carbonic anhydrase II), has shown that after pancreatic duct ligation (PDL), a population of less differentiated ductal cells emerges that expresses Pdx1 and contributes to islets [113]. PDL also causes up-regulation of the embryonic pancreas transcription factor Ngn3 in the ductal cells, and direct lineage tracing has also found that these cells can become insulin-positive cells [114].…”
Section: Digestive Tractmentioning
confidence: 99%